2014
DOI: 10.3109/02699052.2014.910700
|View full text |Cite
|
Sign up to set email alerts
|

Is hydrokinesitherapy effective on gait and balance in patients with stroke? A clinical and baropodometric investigation

Abstract: Hydrokinesytherapy may be considered a promising treatment in improving gait and balance in individuals following stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 21 publications
0
37
0
1
Order By: Relevance
“…31,47,59,69,79 Non-paretic limb swing time was reported in only two studies 59,73 and was not statistically significant in either.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…31,47,59,69,79 Non-paretic limb swing time was reported in only two studies 59,73 and was not statistically significant in either.…”
Section: Resultsmentioning
confidence: 83%
“…Seven of those studies found a statistically significant change in this variable. 29,46,47,55,59,66,69 More specifically, paretic double limb support was reported and statistically significant in four other included studies. 49,50,58,64 Additionally, three of those four studies reported non-paretic double limb support, all exhibiting statistically significant changes.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…exercícios do método Halliwick 15 e hidrocinesioterapia 16 que demonstraram os benefícios do ambiente aquático na recuperação mobilidade, do equilíbrio e do condicionamento cardiovascular em sujeitos com sequelas de AVE 10,17 .…”
Section: Discussionunclassified